Elevated CO2 Has Little Influence on the Bacterial Communities Associated With the pH-Tolerant Coral, Massive Porites spp. - O’Brien, Paul A.; Smith, Hillary A.; Fallon, Stewart; Fabricius, Katharina; Willis, Bette L.; Morrow, Kathleen M.; Bourne, David G. (Frontiers in Microbiology, 2018)
Ocean acidification as a result of increased anthropogenic CO2 input into the atmosphere carries consequences for all ocean life. Low pH can cause a shift in coral-associated microbial communities of pCO2-sensitive corals, however it remains unknown whether the microbial community is also influenced in corals known to be more tolerant to high pCO2/low pH. This study profiles the bacterial communities associated with the tissues of the pCO2-tolerant coral, massive Porites spp., from two natural CO2 seep sites in Papua New Guinea. Amplicon sequencing of the hypervariable V3-V4 regions of the 16S rRNA gene revealed that microbial communities remained stable across CO2 seep sites (pH=7.44-7.85) and adjacent control sites (ambient pH=8.0-8.1). Microbial communities were more significantly influenced by reef location than pH, with the relative abundance of dominant microbial taxa differing between reefs. These results directly contrast with previous findings that increased CO2 has a strong effect on structuring microbial communities. The stable structure of microbial communities associated with the tissues of massive Porites spp. under high pCO2 / low pH conditions confirms a high degree of tolerance by the whole Porites holobiont to ocean acidification, and suggest that pH tolerant corals such as Porites may dominate reef assemblages in an increasingly acidic ocean.